Pengembangan Objek Wisata Tarabunga Kabupaten Toba Berbasis Partisipasi Masyarakat Lokal Tahun 2023 - Titi Rohani Napitupulu; Robert Juni Tua Sitio; Maringan Sinambela; Rusmauli Simbolon; Mery Silalahi (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
The aim of this research is to determine the supporting and inhibiting factors in developing a tarabunga tourist attraction based on local community participation. This research uses a qualitative method with a descriptive approach and data collection techniques through observations and interviews with nine informants. The results of this research describe the supporting and inhibiting factors in efforts to develop tourist attractions based on local community participation. Supporting factors include the provision of opportunities to the community, the will of the community, the ability of the community, cooperation and support from the government. The supporting factors for developing this tourist attraction are very good to be implemented and applied at the location of the Tarabunga tourist attraction and this is done well by some of the community. Meanwhile, inhibiting factors include different work backgrounds, causing individuals to be busy, lack of knowledge and insight regarding the development of the tarabunga tourist attraction, making it difficult for them to participate in the development of the tarabunga tourist attraction, lack of funds or limited funds making it difficult to implement tourism development programs and infrastructure is hampered. Efforts are being made to develop the Tarabunga tourist attraction based on community participation. We must pay attention to what are indicators of community participation-based tourist attraction development, namely the formation of Village-Owned Enterprises (BUMDES), deliberation and outreach, economic empowerment for local communities, and the importance of maintaining the culture and environment of tourist attractions. Community participation in efforts to develop the Tarabunga tourist attraction can be done through various forms of contribution, such as providing ideas, energy, expertise, money and goods.